English language knowledge as a determinant of employability in hotel industry – The case of Vrnjačka Banja, Serbia - Pešić, Dragana (Hotel and Tourism Management, 2022)
English has become widely accepted as the language of hotel industry and one of the core soft skills of employability. Since the perceptions of different stakeholders in education often differ to a certain extent, when designing a language course at a university level, it is of utmost importance to take into consideration the opinion of industry practitioners. The aim of the present diagnostic quantitative study employing case study methodology is to look into the importance of English language knowledge for employability in the hotel industry, define field-specific foreign language needs and identify the problems faced in supplier-consumer encounters. The obtained results point to the fact that hotel employees find English important for successful performance. The most necessary skills proved to be speaking and listening comprehension, followed by writing and reading. The identified problems faced in communication were related to inability to understand the interlocutor and the lack of proper lexical knowledge.